Nul negentienhonderd vijf en zestig : deel 1 : teksten, deel 2 : foto's. - Alviani, Getulio; Arman; Armando; Brown, Gordon; Bury, Pol; Castellani, Enrico; Dorazio, Piero; Fontana, Lucio; Haacke, Hans; Klein, Yves; Kusama, Yayoi; Mack, Heinz; et al. (Amsterdam : Stedelijk Museum Amsterdam, 1965)
Alviani, Getulio ; Anceschi, Giovanni ; Arman ; Armando ; Boriani, Davide ; Bury, Pol ; Castellani, Enrico ; Colombo, Gianni ; Dorazio, Piero ; Fontana, Lucio ; Haacke, Hans ; Kanayama, Akira ; Klein, Yves ; Kusama Yayoi ; Mack, Heinz ; Manzoni, Piero ; Motonaga, Sadamasa ; Murakami, Saburo ; Peeters, Henk ; Piene, Otto ; Rickey, George ; Schoonhoven, Jan ; Shimamoto, Shozo ; Soto, Jesus Rafael ; Tanaka, Atsuko ; Uecker, Günther ; Varisco, Grazia ; de Vecchi, Gabriele ; Vigo, Nanda ; Yamasaki, Tsuruko ; Yoshihara, Michio
Nul negentienhonderd vijf en zestig : deel 2 : foto's
biog. per kunstenaar
Nul 1965 /Zero 1965, Stedelijk Museum Amsterdam, 15 april - 8 juni 1965
Duits & Engels & Frans & Italiaans & Nederlands
boek